YELLOW PITAYA (HYLOCEREUS MEGALANTHUS) FATTY ACIDS COMPOSITION FROM ECUADORIAN AMAZONIA - Jl, Altuna; M, Silva; M, Alvarez; Mf, Quinteros; D, Morales; Carrillo, Wilman (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to determine the composition of methyl esters fatty acids (FAMEs) in yellow pitaya (Hylocereus megalanthus) seeds cultivated in the Palora, Ecuador Amazonian region. Methods: Yellow pitaya oil was obtained from yellow pitaya seeds using the Soxhlet technique. FAMEs identification and quantification were carried out using the gas chromatography (GC) with mass spectrometry (MS) and the database Library NIST14.L to identify the FAMEs present in yellow pitaya oil. Results: Yellow pitaya oil from Ecuador Amazonian region was analyzed by GC-MS, to obtain the five main fatty acids, palmitic acid (11.52%), stearic acid (4.29%), oleic acid (11.09%), vaccenic acid (3.08%), and linoleic acid (69.98%). Omega 6 was the most abundant fatty acid, total content in yellow pitaya seeds oil. Conclusions: Yellow pitaya seeds content a good proportion of polyunsaturated fatty acids (omega 6). For their fatty acid composition, yellow pitaya seeds can be considered as healthy food and can be used in the food industry for different purposes. Regular consumption of yellow pitaya can improve human health.